2014
DOI: 10.1002/anie.201309855
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Intermolecular Azide–Alkyne Cycloaddition of Internal Thioalkynes under Mild Conditions

Abstract: An iridium-catalyzed azide-alkyne cycloaddition reaction (IrAAC) of electron-rich internal alkynes is described. It is the first efficient intermolecular AAC of internal thioalkynes. The reaction exhibits remarkable features, such as high efficiency and regioselectivity, mild reaction conditions, easy operation, and excellent compatibility with air and a broad spectrum of organic and aqueous solvents. It complements the well-known CuAAC and RuAAC click reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(148 citation statements)
references
References 61 publications
2
146
0
Order By: Relevance
“…This catalyst was used to prepare 1,4,5-trisubstituted triazoles M a n u s c r i p t 20 subsequent to Pd-catalyzed Suzuki-Miyaura reactions with appropriate arylboronic acids. Ding et al compared various Ir complexes in the IrAAC of electron-rich internal alkynes and showed that the use of [Ir(cod)Cl] 2 optimized the reaction [104]. The increase of steric hindrance on the alkyne did not affect the reaction efficiency, but an electronic effect was also observed, i.e.…”
Section: The Iraac Reactionsmentioning
confidence: 99%
“…This catalyst was used to prepare 1,4,5-trisubstituted triazoles M a n u s c r i p t 20 subsequent to Pd-catalyzed Suzuki-Miyaura reactions with appropriate arylboronic acids. Ding et al compared various Ir complexes in the IrAAC of electron-rich internal alkynes and showed that the use of [Ir(cod)Cl] 2 optimized the reaction [104]. The increase of steric hindrance on the alkyne did not affect the reaction efficiency, but an electronic effect was also observed, i.e.…”
Section: The Iraac Reactionsmentioning
confidence: 99%
“…Recently, Ding et al reported an iridium catalysed azide-alkyne cycloaddition of electron-rich internal alkyne highly regioselective towards the 1,5-isomer. 17 Unfortunately, due to their toxicity, the use of transition metals has limited the application of click-chemistry in biological systems, but fortunately this situation has spurred the development of several metal free synthetic methods.…”
Section: Generalitymentioning
confidence: 99%
“…A simple and practical method for the preparation of 11 novel phenylsulfonyl substituted triazoles carrying a 3-p-substituted phenyl-1,2,4-oxadiazole unit and 10 novel bis dihydropyrrolo [3,4-d] [1,2,3]triazole-4,6(3aH,5H )-diones carrying a 3-para-substituted phenyl-1,2,4-oxadiazole unit is introduced. The target compounds were assayed against MCF-7 breast cancer cells, but IC 50 values were not low.…”
Section: Resultsmentioning
confidence: 99%